PENERAPAN SISTEM INFORMASI RUANG BELAJAR (SIRUBEL) SEBAGAI UPAYA EFEKTIVITAS BELAJAR SISWA - Ibnur Rusi; Nurul Mutiah; Muhammad Rezal Sultan; Yazid Ridwan; Meizhar Riswanda; Andina Rahmawati; Listia Febrina; Defa Adelia Putri (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2023)
Information and Communication Technology (ICT) innovations in education continue to be encouraged. Many information systems are made with the aim of facilitating the learning process for students. Sungai Raya Village, Kuburaya Regency is a village that continues to make efforts to make it easier for its people in every service provided, including education. Sungai Raya Village already has a website and village service information system, but does not yet have an information system that makes it easier for students to access learning materials. This PKM aims to build, develop an information system, and assist in using the system systematically and organized, making it easier for students in Sungai Raya Village to access knowledge. The PKM method is Community Based Research (CBR) which emphasizes providing solutions to problems based on community needs. The result of PKM is the availability of SIRUBEL that students and the people of Sungai Raya Village can use.